KARAKTERISTIK FISIKOKIMIA NUGET NABATI BERBASIS KACANG ARAB DAN AKAR LOTUS DENGAN VARIASI JENIS FILLER [PHYSICOCHEMICAL CHARACTERISTICS OF CHICKPEA AND LOTUS ROOT PLANT-BASED NUGGETS WITH A VARIETY OF FILLER TYPES] - Soedirga, Lucia Crysanthy; Cornelia, Melanie (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2022)
Chicken nuggets are the most common type of meat-based product that is commonly sold in the market, however, chicken nuggets are not suitable for vegetarian groups. Therefore, it is necessary to find another raw material as an alternative in the making of plant-based nuggets. However, the selection of raw materials in the making of plant-based products often does not emphasize the diversification aspect. Food diversification needs to be improved as an effort to encourage people to diversify their food so that they do not focus on only one type. Chickpeas and lotus root, as well as local starch sources such as tapioca, sago, and corn-starch, are examples of alternative materials that can be used to enhance the diversification aspect in the making of plant-based nuggets. The aim of this study was to determine the selected ratio of chickpea paste and lotus slices along with other types of fillers to make plant-based nuggets based on the physicochemical characteristics. The results showed chickpea paste and sliced lotus root at a ratio of 75:25 with corn-starch as a filler produced plant-based nuggets with physicochemical characteristics: hardness 165.21±7.82 g.force; springiness 0.37±0.01 mm; cohesiveness 0.59±0.03 kg.sec., lightness of 52.71±2.11 and a frying loss of 8.21±2.15%. The moisture, fat, protein, ash, carbohydrate (by difference), and fiber content of selected formulation of nuggets were 40.20±0.42%, 6.73±0.04%; 7.38±0.15%, 3.44±0.02%, 42.16±0.54%, 8.49%; respectively.BAHASA INDONESIA ABSTRACT:Nuget ayam merupakan jenis olahan daging yang banyak dijual di pasaran namun tidak cocok untuk dikonsumsi oleh kelompok vegetarian. Hal ini mendorong adanya alternatif mencari bahan baku lain dalam pembuatan produk nuget nabati, tetapi, pemilihan alternatif bahan pada produk non-daging seringkali tidak memperhatikan aspek diversifikasi. Diversifikasi pangan perlu ditingkatkan sebagai upaya untuk mendorong masyarakat dalam memvariasikan makanan agar tidak terfokus pada satu jenis saja. Kacang arab dan akar lotus serta sumber pati lokal seperti tepung tapioka, tepung sagu, dan tepung maizena merupakan contoh alternatif bahan yang dapat digunakan sekaligus meningkatkan aspek diversifikasi dari pembuatan nuget nabati. Tujuan dari penelitian ini adalah untuk menentukan rasio pasta kacang arab dan irisan lotus serta jenis filler terpilih dalam pembuatan nuget nabati berdasarkan karakteristik fisikokimianya. Hasil penelitian menunjukkan pasta kacang arab dan irisan akar lotus pada rasio 75:25 dengan tepung maizena sebagai filler menghasilkan nuget nabati dengan karakteristik fisikokimia, yakni hardness 165,21±7,82 g.force; springiness 0,37±0,01 mm; cohesiveness 0,59±0,03 kg.sec., lightness 52,71±2,11  dan frying loss 8,21±2,15%. Kadar air, kadar lemak, kadar protein, kadar abu, kadar karbohidrat (by difference), dan kadar serat pangan nuget nabati formulasi terpilih masing-masing sebesar 40,20±0,42%; 6,73±0,04%; 7,36±0,02%, 3,44±0,02%, 42,24±0,54%, 8,49%.